Mechanical Characterization and In Vitro Assay of Biocompatible Titanium Alloys - Iustinian Baltatu; Andrei Victor Sandu; Maria Daniela Vlad; Mihaela Claudia Spataru; Petrica Vizureanu; Madalina Simona Baltatu (Micromachines, 2022)
Metals that come into contact with the body can cause reactions in the body, so biomaterials must be tested to avoid side effects. Mo, Zr, and Ta are non-toxic elements; alloyed with titanium, they have very good biocompatibility properties and mechanical properties. The paper aims to study an original Ti20Mo7ZrxTa system (5, 10, 15 wt %) from a mechanical and in vitro biocompatibility point of view. Alloys were examined by optical microstructure, tensile strength, fractographic analysis, and in vitro assay. The obtained results indicate very good mechanical and biological properties, recommending them for future orthopedic medical applications.